COVID-19 and Human Security: Western Populism, Chinese Strong State and Africa2019;s Submissive Populace (Global Journal of Human-Social Science, 2022)
The COVID-19 has been one pandemic that has greatly impacted the world and its economies since it was identified in 2019 This current research therefore sets out to investigate the COVID- 19 and Human Security in relation to western populism Chinese strong state and Africa s submissive populace The study was undertaken in the University of Cape Coast UCC which is a diverse community of both Africans and Euro-Asians Three categories of respondents are involved in this study namely Africans mainly Ghanaians Euro-Americans and Chinese Purposive sampling technique was used to interview respondents who are Chinese and Euro- American since they form a very small population and need to be specifically identified The study also adopted simple random sampling for the respondents who are African mainly Ghanaians in a survey research The study revealed that China s strong state in defeating the virus could be attributed to mandatory testing and quarantine for 14 days on arriving in China Again China was able to defeat the virus because of mobile hospitals and mandatory vaccination that the government implemented The Western world could not contain the spread and fatality rate of the virus because of their disregard to ensuring and following social distancing and other COVID-19 protocols and their insistence for their rights and freedom to engage in social life Africa on the other hand submitted to the virus and learnt from the devastating experiences of the West and implemented policies to contain and control the spread of the pandemic Policies such as strict enforcement of the adherence to the COVID-19 protocols and provision of quarantine and isolation centres for infected people account for Africa s submissive populace and her ability to contain the virus Recommendations have been made for policy implication and this includes governments could consider rolling out mobile hospitals to provide health care assistance to their citizens provision of free testing and vaccination and investment in research to develop and come up with vaccination and medication for the COVID-19 virus
Keywords: covid-19; human security; western populism; chinese strong state; africa2019; s submissive populace; university of cape coast